Peran Vitamin D dalam Retinopati Diabetik - Michelle Amelia Tanian; Felix Rowan; Santi Anugrahsari; Rendy Damar Nugraha (Jurnal MedScientiae, 2023)
Diabetic retinopathy (RD) is the most common microvascular complication and can cause visual impairment and even blindness. Various studies show a relationship between vitamin D deficiency and increased incidence of RD. The purpose of this scientific paper is to explore the role of vitamin D in relation to RD so as to open opportunities for further knowledge and research. Research Methods using Literature Review, by searching PubMed and Google Scholar, with keywords in English "vitamin D" or "cholecalciferol" or "25-hydroxyvitamin D" and "diabetic retinopathy". In the discussion it was discussed that vitamin D plays a protective role in the development of diabetic retinopathy through its anti-inflammatory and anti-angiogenic properties. For future research, it is hoped that it will further explore the role of Vitamin D in relation to Diabetic retinopathy.